2022
DOI: 10.3389/fmars.2022.900200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Stress Induces Tissue Damage, Immune Defense, and Oxygen Transport Change in Gill of Silver Carp (Hypophthalmichthys molitrix): Evaluation on Hypoxia by Using Transcriptomics

Abstract: The silver carp (Hypophthalmichthys molitrix) is an economically, as well as environmentally, important fish that harbors low environmental hypoxia tolerance and frequently contributes to a loss of aquaculture productivity. The gill is the first tissue attacked by hypoxia; however, the response of the gills of H. molitrix to hypoxia stress at the tissue, cellular, and molecular levels has not been clearly established. The influence of hypoxia on histological features along with gene expression in silver carp g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…KEGG analysis showed that 14 pathways were significantly enriched (FDR <0.05), which were mainly involved in carbohydrate metabolism, endocrine system, endocrine and metabolic disease ( Supplementary Table S8 ). Notably, the HIF-1 signaling pathway, a key pathway in the hypoxia response, was also significantly enriched ( Li et al, 2022 ). In high temperature stress transcriptome, 18,832 unique genes were identified from six DNA libraries (WC1, WC2, WC3, WT1, WT2, WT3), including 2,718 DEGs (foldchange >2, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KEGG analysis showed that 14 pathways were significantly enriched (FDR <0.05), which were mainly involved in carbohydrate metabolism, endocrine system, endocrine and metabolic disease ( Supplementary Table S8 ). Notably, the HIF-1 signaling pathway, a key pathway in the hypoxia response, was also significantly enriched ( Li et al, 2022 ). In high temperature stress transcriptome, 18,832 unique genes were identified from six DNA libraries (WC1, WC2, WC3, WT1, WT2, WT3), including 2,718 DEGs (foldchange >2, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The mapping rate, coverage, and sequencing depth of the filtered data were analyzed. We further filtered the calls using GATK VariantFiltration (Lin et al, 2022) with the following parameters: QD < 2.0, FS > 60.0, MQ < 40.0, MQRankSum < −12.5, ReadPosRankSum < −8.0. Mutational positions, genomic regions, and potential amino acid changes were assessed using ANNOVAR (v2019).…”
Section: Variation Detection and Annotationmentioning
confidence: 99%
“…However, the need for this type of intervention (e.g., increased aeration or oxygenation) may be greater in fish species with higher oxygen requirements (e.g., salmonids). Furthermore, it is worth noting that exposure of both, oxygen sensitive salmonids 95 and less oxygen sensitive cyprinids 96 or pike perch 97 to hypoxia modulates immune responses and reduces or delays them. For example, during peritonitis hypoxia impaired the influx of lymphocytes to the peritoneal niche in the later phases of the immune reaction in pikeperch while pro‐inflammatory immune responses manifested as mobilisation of myeloid cells, and expression of pro‐inflammatory mediators was less severely affected 97 …”
Section: Impact Of a Poxvirus Gill Infection On Respiratory Functionmentioning
confidence: 99%
“…Fish gills acted as an important role in physiological functions including gaseous exchange, osmoregulation, acid–base regulation, excretion of nitrogenous waste, and hormone production [ 3 , 4 ]. Gills are also the main organs that respond to the change in dissolved oxygen in the aquatic environment [ 5 ]. It was reported that the morphological structures of gills in many fish showed significant changes during hypoxia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%